Changes in hemoglobin oxidation and band 3 during blood storage impact oxygen sensing and mitochondrial bioenergetic pathways in the human pulmonary arterial endothelial cell model - Jana, Sirsendu; Kassa, Tigist; Wood, Francine; Hicks, Wayne; Alayash, Abdu I. (Frontiers in Physiology, 2023)
Red blood cells (RBCs) undergo metabolic, oxidative, and physiological changes during storage, collectively described as the “storage lesion.” The impact of storage on oxygen homeostasis, following transfusion, is not fully understood. We show that RBC storage induces changes in oxygen binding that were linked to changes in oxygen sensing (hypoxia-inducible factor, HIF-1α) mechanisms and mitochondrial respiration in human pulmonary arterial endothelial cells (HPAECs). A decrease in oxygen affinity (P50) to approximately 20 from 30 mmHg was seen at the first week but remained unchanged for up to 42 days. This led to the suppression of HIF-1α in the first 3 weeks due to limited oxygen supplies by RBCs. Furthermore, membrane oxidative damage, band 3 alterations, and subsequent microparticle (MP) formation were also noted. Mass spectrometric analysis revealed the upregulation of transitional endoplasmic reticulum ATPase, essential for clearing ROS-damaged membrane proteins and the protein DDI1 homolog, a proteasomal shuttle chaperone. Band 3 complex proteins and superoxide dismutase were among the downregulated proteins. Mitochondrial oxygen consumption rates measured in HPAECs incubated with RBC-derived MPs (14-day and 42-day) showed a rise in maximal respiration. Intervention strategies that target intracellular hemoglobin (Hb)’s redox transitions and membrane changes may lead to the reestablishment of oxygen homeostasis in old RBCs.